The combination tea of corn silk (Zea mays L.) and rosella flowers (Hibiscus sabdariffa L.): Antioxidant levels using different drying methods - Ulmillah, Aulia; Suri, Intan Mulia; Kamelia, Marlina; Pawhestri, Suci Wulan (Univeritas Papua, 2022)
Corn silk and rosella flowers are plants whose utilization can still be developed, especially in the food sector. The secondary metabolites found in both plants serve as a source of natural antioxidants to combat free radicals. This study aims to examine the effect of variations in drying methods on the antioxidant activity content of a combination tea of corn silk and rosella flower. Antioxidant level test using the DPPH method. Analysis of antioxidant data in the form of determining the IC50 value using probit linear regression analysis. The study results show that drying using the oven method has an IC50 of 83 ppm while drying in the sun has an IC50 of 121 ppm. Research findings indicate high antioxidant levels in a combination of corn silk and rosella flower tea through oven drying and moderate antioxidants in direct drying in the sun.